Comparison of Tumor Seeding and Recurrence Rate After Laparoscopic vs. Open Nephroureterectomy for Upper Urinary Tract Transitional Cell Carcinoma - Morselli, Simone; Vitelli, Ferdinando Daniele; Verrini, Giorgio; Sebastianelli, Arcangelo; Campi, Riccardo; Liaci, Andrea; Spatafora, Pietro; Barzaghi, Paolo; Ferrari, Giovanni; Gacci, Mauro; Serni, Sergio; Brausi, Maurizio (Frontiers in Surgery, 2021)
INTRODUCTION: Laparoscopic surgery for Upper Urinary Tract Urothelial Cell Carcinoma (UTUC) is still debated for its possible seeding risk and thus consequent oncological recurrences, especially for atypical ones. Aim of the study is to compare recurrence and survival after Laparoscopic vs Open Radical Nephroureterectomy (RNU) for Upper Urinary Tract Urothelial Cancer (UTUC). METHOD: Retrospective evaluation of UTUC consecutive surgeries from 2008 to 2019 was conducted, including pT≥2, High Grade UTUC, who underwent RNU with bladder cuff excision without concomitant lymphadenectomy in three urological tertiary centers. Statistical analyses compared recurrence and cancer specific survival, based on surgical approach, while logistic multivariate analyses and Kaplan Meyer survival curve analyzed possible risk factors for recurrence and survival. RESULTS: 107 cases of RNU, 47 (43.9%) laparoscopic and 60 (56.1%) open, were included in this report. Preoperative characteristics were comparable between groups, however tumor stage was higher in the Open arm [T3-T4 in 44 (73.3%) vs 20 (43.4%) in Laparoscopic]. Mean follow-up was 91.6 months in laparoscopy versus 93.5 months in open. Recurrence rate (RR) was comparable between groups (p=0.594), and so was the site, although, 3 (6.3%) peritoneal recurrences were found only in laparoscopic group (p=0.057). At multivariate logistic regression, tumor stage and surgical approach were independent predictors of recurrence (p<0.05), while only tumor stage was predictor of cancer specific death (p=0.029). CONCLUSIONː Surgical approach has no impact on recurrence site, overall survival and RR. Still, according to our data peritoneal carcinomatosis was present only in laparoscopic arm, despite it didn’t reached statistical significance.